2007
DOI: 10.1007/s10741-007-9065-7
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the importance of aminopeptidase A in hypertension

Abstract: The renin-angiotensin system (RAS) plays an important role in the maintenance of normal blood pressure and the etiology of hypertension; however, minimal attention has been paid to the degradation of the effector peptide, angiotensin II (AngII). Since aminopeptidase A (APA)-deficient mice develop hypertension APA appears to be an essential enzyme in the control of blood pressure via degradation of AngII. The robust hypertension seen in the spontaneously hypertensive rat (SHR) is due to activation of the RAS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 70 publications
(79 reference statements)
0
29
0
Order By: Relevance
“…These include mannose-binding lectin 2 (MBL2) 49,50) and glutamyl aminopeptidase ENPEP 51,52) . MBL is an important protein of the humoral innate immune system, and it has been reported that the serum MBL concentrations are decreased in obese subjects, accompanied by an increase in inflammatory markers 49) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…These include mannose-binding lectin 2 (MBL2) 49,50) and glutamyl aminopeptidase ENPEP 51,52) . MBL is an important protein of the humoral innate immune system, and it has been reported that the serum MBL concentrations are decreased in obese subjects, accompanied by an increase in inflammatory markers 49) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In addition, G54D MBL2 gene polymorphisms confer an increased risk for developing gestational diabetes mellitus 50) . ENPEP is an enzyme that facilitates the conversion of angiotensin , the main effector protein of the renin-angiotensin-aldosterone system, to angiotensin 51) . In addition, Enpep KO mice develop hypertension, and recombinant ENPEP treatment significantly decreases systolic blood pressure 52) , suggesting that ENPEP is an essential enzyme for controlling blood pressure.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This ectoenzyme, also known as glutamyl aminopeptidase (EC 3.4.11.7), has also been described in cytosolic fractions and body fluids [23,24]. Previous studies have indicated the involvement of APA in immune response as this enzyme is expressed in developing B lymphocytes and regulated by interleukins [25].…”
Section: Discussionmentioning
confidence: 99%
“…1 The development of cardiac fibrosis and subsequent diastolic and systolic dysfunction is a major complication of hypertensive heart disease. It contributes to the progressive disruption of the normal cardiac structure, which results in an increased risk of adverse cardiac events, such as myocardial ischemia, infarction, arrhythmias and sudden cardiac death.…”
mentioning
confidence: 99%